Evidence of Microbursts Observed Near the Equatorial Plane in the Outer Van Allen Radiation Belt - Mykhaylo Shumko; Drew L. Turner; T. P. O'Brien; Seth G. Claudepierre; John Sample; D. P. Hartley; Joseph Fennel; J. Bernard Blake; Matina Gkioulidou; Donald G. Mitchell (Geophysical Research Letters)
Abstract We present the first evidence of electron microbursts observed near the equatorial plane in Earth's outer radiation belt. We observed the microbursts on 31 March 2017 with the Magnetic Electron Ion Spectrometer and Radiation Belt Storm Probes Ion Composition Experiment on the Van Allen Probes. Microburst electrons with kinetic energies of 29–92 keV were scattered over a substantial range of pitch angles, and over time intervals of 150–500 ms. Furthermore, the microbursts arrived without dispersion in energy, indicating that they were recently scattered near the spacecraft. We have applied the relativistic theory of wave‐particle resonant diffusion to the calculated phase space density, revealing that the observed transport of microburst electrons is not consistent with the hypothesized quasi‐linear approximation.